ACCUMULATION OF CADMIUM IONS IN TABLE BEET (BETA VULGARIS L.) PLANTS AS AFFECTED BY THE USE OF FERTILIZERS AND AMELIORANTS - Dydiv, A.; Kachmar, N.; Datsko, T.; Ivankiv, M.; Rosa, R. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The article presents the findings of a study examining how different fertilization systems and calcium-based soil amendments affect the accumulation of cadmium (Cd²⁺) ions in various parts of table beet plants (cv. Bordo Kharkivskyi). This was analyzed under simulated conditions of cadmium contamination in dark-gray podzolic soil in the Western Forest-Steppe of Ukraine. The research assessed the effects of organic, mineral, and organic-mineral fertilization systems, combined with liming, on cadmium mobility in the soil and its uptake by table beet plants. The study calculated the hazard coefficients for mobile Cd²⁺ forms in the soil, cadmium accumulation in plants, and the biological absorption coefficient. Results indicated that increasing the levels of cadmium contamination in the soil - from 1 to 5 maximum permissible concentrations (MPC) – led to a rise in mobile Cd²⁺ forms across all treatments, resulting in greater accumulation of cadmium in table beet plants. Cadmium was found to accumulate most significantly in the underground parts (root tail) and least in the core of the root. Notably, the concentration of Cd²⁺ in the leaf blades was 3.5 to 4.1 times higher than in the root pulp. The study also found that applying organic fertilizers (Biohumus) and mineral fertilizers (Nitroammophoska), along with soil liming (CaCO₃), reduced cadmium mobility in the soil and its accumulation in table beet plants. The lowest concentrations of mobile Cd²⁺ in the soil - and thus the least accumulation of the metal in the roots - were observed with the application of Biohumus at 4 t/ha combined with CaCO₃ at 5 t/ha (treatment 6) and N₃₄P₃₄K₃₄ combined with Biohumus at 2 t/ha and CaCO₃ at 5 t/ha (treatment 7). These results differed significantly from the control group (p < 0.001) and had hazard coefficients of 0.20 and 0.33, respectively. A strong correlation (r = 0.85) was found between the concentration of mobile Cd²⁺ forms in the soil and their content in the table beet plants across all experimental treatments, with a coefficient of determination R²=0.73. The findings of this research can be utilized to optimize agricultural practices in areas contaminated with heavy metals, thereby minimizing the risk of cadmium accumulation in table beet produce.